Possible Association between Vogt-Koyanagi-Harada Disease and Coronavirus Disease Vaccine: A Report of Four Cases - de Queiroz Tavares Ferreira, Felipe; Araújo, Daniel Cunha [UNESP]; de Albuquerque, Leonardo Mendonça; Bianchini, Priscila Monaro; Holanda, Erick Carneiro; Pugliesi, Alisson (Taylor & Francis, 2022)
Vogt-Koyanagi-Harada (VKH) syndrome is an autoimmune, multisystemic disease characterized by severe bilateral granulomatous posterior, which can occur due to viral infection or vaccination. We report four cases that had a likely association between VKH disease and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. Two patients had VKH symptoms within 1 and 2 weeks after receiving the ChAdOx1 nCoV-19 vaccine. One patient presented with VKH symptoms 5 days after receiving the BNT162b2 vaccine, and one patient had symptoms within 4 weeks after receiving the CoronaVac vaccine. Early diagnosis and treatment of VKH disease are essential for the visual prognosis of this aggressive disease. Further in-depth studies are necessary to investigate this likely association to enable ophthalmologists to identify new assumed correlations between the diseases described in this study.
Keywords: Choroiditis; COVID-19; retina; SARS-CoV-2; Uveitis; Vogt-Koyanagi-Harada disease